ANALISIS LITERASI MATEMATIKA SISWA DENGAN GAYA BERPIKIR SEKUENSIAL KONKRET DAN ACAK KONKRET DALAM MENYELESAIKAN SOAL TIPE AKM - Izzati, Nur; Nurhafika; Rahmatina, Desi (Jurnal Riset Pembelajaran Matematika, 2023)
This research aimed to describe the mathematical literacy of students with concrete sequential and concrete random thinking styles in solving AKM-type questions. The type of research used is descriptive research with a qualitative research approach. The subjects of this study were two students of class VIII A at SMP Negeri 17 Bintan consisting of one student each of concrete sequential and concrete random student thinking style. The selection of subjects was based on the results of the best students' mathematical literacy tests from concrete sequential and concrete random thinking styles. Data collection in this study was carried out using questionnaires, tests, and interviews. The research instruments used were a thinking-style questionnaire developed by John Park Le Tellier, AKM-type mathematical literacy test questions, and an interview guide. Data analysis in this study used data reduction, data display, and drawing conclusions. The results of the research show that students with a concrete sequential thinking style were able to meet the cognitive level of mathematical literacy knowing and applying level. Students with a concrete random thinking style are only able to meet the cognitive level of knowing mathematical literacy.